Pengaruh Beban Kerja, Komunikasi Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan Pada Kantor Kecamatan Yang Ada Di Kota Mataram - Nurhidayah; Lalu Mimbar; Surahman Hidayat (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This research aims to determine and analyze the significant partial influence of workload, work communication and work stress on employee satisfaction at the sub-district office in Mataram City. The population in this study was all 157 sub-district office employees in Mataram City. This research uses the Slovin technique because the population is large, so the sample in this research was narrowed so that a sample of 113 respondents at the sub-district office in Mataram City was obtained. The data analysis method used in this research is Multiple Linear Regression. The research results show that: (1) Workload has a partially significant effect on job satisfaction. (2) Communication has a partially significant effect on job satisfaction. (3) Job stress does not have a partially significant effect on job satisfaction.